Postoperative progression of brain metastasis is associated with seizures. Issue 10 (9th August 2022) - Wolpert, Fabian; Grossenbacher, Bettina; Moors, Selina; Lareida, Anna; Serra, Carlo; Akeret, Kevin; Roth, Patrick; Imbach, Lukas; Le Rhun, Emilie; Regli, Luca; Weller, Michael; Galovic, Marian
Abstract: Seizures in patients with brain metastases have an impact on morbidity and quality of life. The influence of tumor growth on the risk of seizures in these patients is not well defined. In this cohort study, we evaluated adult patients from the University Hospital of Zurich following resection of brain metastases from solid tumors, with or without preoperative seizures, at 3, 6, 9, and 12 months postoperatively. Brain magnetic resonance imaging was assessed for tumor progression using the Response Assessment in Neuro‐Oncology criteria. The quarterly risk of unprovoked seizures was modeled with mixed effects logistic regression. We analyzed 444 time frames in 220 patients. Progression of brain metastases was independently associated with seizures during the respective quarterly follow‐up period (odds ratio = 3.9, 95% confidence interval = 1.3–11.3, p  = .014). Complete resection of brain metastases was associated with a lower risk of seizures (odds ratio = .2, 95% confidence interval = .04–.7, p  = .015). Postoperative progression of brain metastases quadrupled the risk of seizures; therefore, vigorous follow‐up may be useful to identify tumor progression and gauge the risk of seizures. The identification of patients at high seizure risk may have implications for treatment decisions and influence aspects of daily life. Breakthrough seizures may indicate brain metastases progression.